Joint throughput and channel aware (TCA) dynamic scheduling algorithm for emerging wearable applications - Alam, Muhammad Mahtab; Ben Arbia, Dhafer; Ben Hamida, Elyes (IEEE Wireless Communications and Networking Conference : [proceedings] : WCNC, 2016)
This paper addresses a reliability concern of the emerging wearable applications under dynamic and realistic conditions. We propose a new joint throughput and channel aware (TCA) dynamic scheduling algorithm for IEEE 802.15.6 standard to enhance the system performance while exploiting m-periodic scheduled access mechanism. First, various mobility patterns are generated with special emphasis on space and time varying links and their performance which are most vulnerable under dynamic environment. A deterministic pathloss values (as an estimate of the channel) are obtained from a set of training sequence which is generated using motion capture system and bio-mechanical modeling. Consequently, signal to noise (SNR), bit error rate (BER) and packet error rate (PER) are calculated. The TCA algorithm during the first phase uses this estimated PER to select the potential nodes for a time slot. Whereas in the second phase, based on the nodes priority and the data packets availability among the potential candidates, finally a slot is assigned to one node. This process is repeated by the coordinating node until the end of the super frame. This scheme has a significant gain over a reference scheme (i.e., without above adaptation). On average, 20-to-55 percent extra packets are received, along with 1-to-5 joules of energy savings though at the cost of higher delay ranging from 20-to-200 ms while operating at low power levels (i.e., 0 dBm, -5 dBm, -10 dBm).